2013
DOI: 10.1590/s1516-05722013000400014
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre as atividades antiradical, antiacetilcolinesterase e teor de fenóis totais de extratos de plantas medicinais de farmácias vivas

Abstract: Palavras-chave: farmácias vivas, acetilcolinesterase, antiradical, doença de AlzheimerABSTRACT: Correlation between the anti-radical, anti-acetylcholinesterase activities and phenolic content of some extracts of live herbal pharmacies in the Northeast of Brazil. The purpose of this study was to evaluate the phenolic content of 18 medicinal plant extracts of "Live Pharmacies" and correlate them with their free radical scavenging activity and inhibition of the acetylcholinesterase enzyme. Higher amounts of pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
1
17
1
7
Order By: Relevance
“…The most common antioxidants present in the foods in our diet are vitamin C, vitamin E, selenium, and carotenoids, and in addition phenolic compounds such as phenolic acids and flavonoids also contribute to antioxidant activity [8]. …”
Section: Introductionmentioning
confidence: 99%
“…The most common antioxidants present in the foods in our diet are vitamin C, vitamin E, selenium, and carotenoids, and in addition phenolic compounds such as phenolic acids and flavonoids also contribute to antioxidant activity [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Para os teores flavonoides, esses autores encontraram valores de 38,44 GAE.mg-1 e 26,04 GAE.mg-1 respectivamente. Morais et al (2013) avaliaram o extrato etanólico de Punica granatum Linn. e relacionaram a atividade antioxidante encontrada ao teor de fenóis totais que correspondeu a 135,89 GAE.mg-1.…”
Section: Discussionunclassified
“…However, Costa et al (2017) evaluated the crude ethanol extract of Croton argyrophyllus, and reported higher total phenol and flavonoid contents with values of 269.72 ± 6.25 mg GAE/g and 98.43 ± 1.39 mg QE/g, respectively. In the same way, Morais et al (2013) analyzed various herbal extracts and found phenolic compound content at 120.27 mg GAE/g extract in Croton zenhtneri ethanolic extract.…”
Section: Antioxidant Activitymentioning
confidence: 99%